2011
DOI: 10.1016/j.jcrs.2011.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Photorefractive keratectomy with mitomycin-C after corneal transplantation for keratoconus

Abstract: No author has financial or proprietary interests in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 58 publications
(68 reference statements)
1
17
0
16
Order By: Relevance
“…The addition of mitomycin C to PRK has improved the corneal haze that may happen after conventional PRK (Fig. 2) [39,40]. Laser-assisted subepithelial keratectomy (LASEK), as an advanced surface ablation, has been also used in the past few years in an attempt to decrease the haze [6,41].…”
Section: Surface Ablationmentioning
confidence: 99%
“…The addition of mitomycin C to PRK has improved the corneal haze that may happen after conventional PRK (Fig. 2) [39,40]. Laser-assisted subepithelial keratectomy (LASEK), as an advanced surface ablation, has been also used in the past few years in an attempt to decrease the haze [6,41].…”
Section: Surface Ablationmentioning
confidence: 99%
“…Hodge and colleagues published a consecutive case series of 41 patients (49 eyes) with refractive cylinders above and below 6.00 D after penetrating keratoplasty (PK) for keratoconus. They reported results comparable to a published series of post‐keratoplasty eyes treated with LASIK, with an eight per cent loss of two lines of visual acuity and no cases of severe haze. Similarly, Ward and colleagues in a retrospective case review of 20 eyes with post‐keratoplastic anisometropia reported 100 per cent patient satisfaction with 90 per cent having a visual acuity of better than 6/12, 50 per cent of eyes gaining one to two lines of visual acuity, a mean reduction in astigmatism of 2.9 D and loss of two lines of visual acuity in a single eye.…”
Section: Surface Ablation In Eyes With Previous Corneal Surgerymentioning
confidence: 99%
“…The primary measures of success following corneal transplant surgery are visual acuity and graft survival. Secondary measures include residual astigmatism and mean spherical equivalent refraction . Residual astigmatism following penetrating corneal transplantation appears to be relatively consistent .…”
Section: Special Indications For Lasik Surgerymentioning
confidence: 99%
“…Marked corneal vascularisation of the host tissue, wound ectasia and wound malposition represent relative contraindications to LASIK following penetrating corneal grafts . Surface ablation may be indicated over LASIK in some patients and can provide excellent visual outcomes, further removing the risk of keratome‐related complications . The use of topography‐based surface ablations in conjunction with mitomycin C has shown further promise in correcting these errors .…”
Section: Special Indications For Lasik Surgerymentioning
confidence: 99%
See 1 more Smart Citation